Promoting Effect of Palladium on ZnAl2O4-Supported Catalysts Based on Cobalt or Copper Oxide on the Activity for the Total Propene Oxidation - Ocsachoque, Marco Antonio (2021)
Palladium-modified Co-ZnAland Cu-ZnAl materials were used and found active for the catalytic oxidation of propene and propane. According to the results obtained by XRD, TPR and XPS, the zinc aluminate-supported phases are oxide phases, Co3O4, CuO and PdOx for Co-ZnAl, Cu-ZnAl and Pd-ZnAl catalysts, respectively. These reducible oxide species present good catalytic activity for the oxidation reactions. The addition of palladium to Co-ZnAl or Cu-ZnAl samples promoted the reducibility of the system and, consequently, produced a synergic effect which enhanced the activity for the propene oxidation. The PdCo-ZnAl sample was the most active and exhibited highly dispersed PdOx particles and surface structural defects. In addition, it exhibited good catalytic stability. The H2 pre-treated PdCu-ZnAl, PdCo-ZnAl and Pd-ZnAl samples showed higher activity than the original oxide catalysts, evidencing the important role of the oxidation state of the species, mainly of the palladium species, on the catalytic activity for the propene combustion. The synergic effect between metal transition oxides and PdOx could not be observed for the propane oxidation.